Anti-infective efficacy, cytocompatibility and biocompatibility of a 3D-printed osteoconductive composite scaffold functionalized with quaternized chitosan. (December 2016) - Yang, Ying; Yang, Shengbing; Wang, Yugang; Yu, Zhifeng; Ao, Haiyong; Zhang, Hongbo; Qin, Ling; Guillaume, Olivier; Eglin, David; Richards, R. Geoff; Tang, Tingting
Graphical abstract: Abstract: Contaminated or infected bone defects remain serious challenges in clinical trauma and orthopaedics, and a bone substitute with both osteoconductivity and antibacterial properties represents an improvement for treatment strategy. In this study, quaternized chitosan (hydroxypropyltrimethyl ammonium chloride chitosan, HACC) was grafted to 3D-printed scaffolds composed of polylactide- co -glycolide (PLGA) and hydroxyapatite (HA), in order to design bone engineering scaffolds endowed with antibacterial and osteoconductive properties. We found that both the PLGA/HA/HACC and PLGA/HACC composite scaffolds decreased bacterial adhesion and biofilm formation under in vitro and in vivo conditions. Additionally, ATP leakage assay indicated that immobilizing HACC on the scaffolds could effectively disrupt microbial membranes. Using human bone marrow-derived mesenchymal stem cells (hBMSCs), we demonstrated that HA incorporated scaffolds, including PLGA/HA and PLGA/HA/HACC, favoured cell attachment, proliferation, spreading and osteogenic differentiation compared to HA-free PLGA or PLGA/HACC scaffolds. Finally, an in vivo biocompatibility assay conducted on rats, showed that HA incorporated scaffolds (including PLGA/HA and PLGA/HA/HACC scaffolds) exhibited good neovascularization and tissue integration. Taken together, our findings support the approach for developing porous PLGA/HA/HACC composite scaffold with potential clinical application in the treatment of infected bone. Statement of Significance: Although plenty of conductive scaffold biomaterials have been exploited to improve bone regeneration under infection, potential tissue toxicity under high concentration and antibiotic-resistance are their main deficiencies. This study indicated that HACC-grafted PLGA/HA composite scaffold prepared using an innovative 3D-printing technique and covalent grafting strategy showed significantly enhanced antibacterial activities, especially against the antibiotic-resistant strains, together with good osteogenic activity and biocompatibility. Therefore, it provides an effective porous composite scaffold to combat the infected bone defect in clinic with decreased risks of bacterial resistance and open a feasible strategy for the modification of scaffold interfaces involved in the bone regeneration and anti-infection.